Perlindungan Korban Pelecehan Seksual Melalui Pendidikan Dan Tindakan Hukum - Debbie Aldama; Kiara Anemadya Jaelani; Viki Kosasih (Universitas Katolik Widya Karya Malang, 2023)
This journal discusses efforts to improve the protection of victims of sexual harassment through education and legal action. The research was conducted by collecting data through interviews with victims of sexual harassment and legal experts. The research results show that proper education and effective legal action are very important in providing protection to victims of sexual harassment. In addition, strong cooperation is needed between government agencies, communities and families to ensure the safety and welfare of victims. This journal provides recommendations to increase public awareness about the importance of protecting victims of sexual harassment and strengthen existing legal measures to protect victims. It is hoped that the results of this research can assist in efforts to protect victims of sexual harassment and strengthen the existing protection system.